Influencer Jejouw's Self-Presentation on Instagram Social Media in an Effort to Build Personal Branding - Putra Adywibawa, Rangga Aru; Maylanny Christin (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research investigates the personal branding and impression management practices implemented by Jejouw influencers on the social media platform Instagram, using Erving Goffman's dramaturgical theory approach. Jejouw is used as a study subject to reveal how he builds and maintains a consistent personal image. The research method used is a descriptive qualitative approach, including in-depth interviews and analysis of Jejouw's Instagram content. The research results show that Jejouw succeeded in playing a complex role in public (front stage), by managing the desired impression through the content he published. Behind the scenes (backstage), Jejouw shows a more authentic and personal side to his followers. This study provides insight into how influencers use social media to build strong relationships with their audiences, influencing followers' opinions and behavior. With practical and theoretical implications, this research recommends further development of dramaturgical theory in a digital context, as well as the implementation of more structured impression management strategies for influencers and digital marketing practitioners. This is expected to increase understanding of the dynamics of social interaction and personal branding practices in the ever-growing social media era.